Willeboer en die Boere-Franse: mitifisering en ontnugtering in Villebois-Mareuil se Carnet de Campagne - Morgan, Naomi (University of the Free State, 2000)
The commemoration of the Anglo-Boer War provides researchers with an opportunity to publicise lesser known and forgotten texts. Worthy texts by foreign participants in the war are scarce; Villebois-Mareuil 's Carnet de Campagne is the work of a dedicated soldier, an author in his own right and the model for one of the bestknown figures on the French stage, Cyrano de Bergerac. This article focuses on Villebois's changing view of the Boers. The reader is provided with lengthy quotations from the war diary, for the most part accessible for the first time in Afrikaans. It becomes clear that Villebois's view of the Boers is coloured by personal considerations (his desire for military glory and his view of the Boers as distant descendants of the French). What Villebois and Bergerac have in common, and what becomes clear from his changing view of the Boers in this diary, is their personal striving for excellence and their gradual disillusionment with the human material by means of which military glory was to be achieved on the battle-field.

Die herdenking van die Anglo-Boereoorlog bied aan navorsers die geleentheid om minder bekende en vergete rekste onder belangstellendes se aandag ce bring. Goeie tekste deur buitelandse deelnemers aan die oodog is skaars; Villebois-Mareuil se Kampanje-joernaal is die werk van 'n coegewyde soldaar, 'n skrywer in eie reg en die model vir een van die bekendste silhoeecre op die Franse verhoog, Cyrano de Bergerac. In hierdie artikel word daar gekonsentreer op Villebois se vecanderende siening van die Beere. Die leser word voorsien van lang aanhalings uic die joernaal, waarvan die meeste vir die eerste keer in Afrikaans verskyn. Daaruit blyk die dat Villebois se siening van die Boere gekleur word deur persoonlike oorwegings (sy behoefre aan militere glorie, sy siening van die Boere as verloopte Franse). Wat illebois en Bergerac gemeen her, en wat duidelik blyk uit sy veranderende siening van die Boer in hierdie joernaal, is 'n persoonlike srrewe na uitmuntendheid en 'n geleidelike ontgogeling met die mensemateriaal waarmee milirere glorie op die slagveld behaal moes word.
Keywords: Villebois' vigorous; Boer; Famous Boers; Villebois-Mareuil 's Carnet de Campagne